Inexpensive Bismuth-Film Electrode Supported on Pencil-Lead Graphite for Determination of Pb(II) and Cd(II) Ions by Anodic Stripping Voltammetry - Karen C. Bedin; Edson Y. Mitsuyasu; Amanda Ronix; André L. Cazetta; Osvaldo Pezoti; Vitor C. Almeida (International Journal of Analytical Chemistry)
The present work reports the development and application of bismuth-film electrode (BiFE), obtained by in situ method on the pencil-lead graphite surface, for simultaneous Cd(II) and Pb(II) determination at trace levels, as alternative to replace the mercury-film electrodes. Experimental factors, deposition time (td), deposition potential (Ed), and Bi(III) concentration (CBi), were investigated by applying a 23 factorial design using 0.10 mol/L acetate buffer solution (pH 4.5) as supporting electrolyte. The analysis conditions of the differential pulse technique were td = 250 s, Ed = -1.40 V, and CBi = 250 mg L−1. The validation of the method employing BiFE was accomplished by determination of merit figures. The detection limits were of 11.0 μg L−1 for Cd(II) and 11.5 μg L−1 for Pb(II), confirming that proposed method is attractive and suitable for heavy metals determination. Additionally, the BiFE developed was successfully applied for the Cd(II) and Pb(II) determination in wastewater sample of battery industry.